Understanding the lived experiences of children with diaspora parents in Bulawayo, Zimbabwe - Mthokozisi Moyo; Phumuzani Mpofu (International Review of Social Sciences Research)
Migration has reshaped family structures globally, giving rise to transnational families in which parents migrate for economic, social, or political reasons, leaving children behind. In Bulawayo, Zimbabwe, the ongoing economic crisis has led to increased parental migration, creating challenges for children left behind. This study explored their emotional, social, and economic realities. It examines the psychosocial impacts of parental absence, including feelings of abandonment, emotional detachment, and exposure to negative peer influences. While remittances offer financial stability and access to education, they cannot replace parental emotional support, often resulting in behavioural and identity struggles. This study used a qualitative approach aimed at understanding and improving the real-life experiences of children, parents, and key stakeholders. Guided by a transformative perspective, which focuses on promoting social change and giving voice to marginalized groups, the research applied Participatory Action Learning and Action Research (PALAR) to actively involve participants in the learning and problem-solving process. Data were collected through interviews and focus groups. Findings reveal that while some children show resilience, others face emotional distress, financial instability, and lack of parental supervision. Digital communication helps but is insufficient for maintaining parent-child bonds. The study recommends interventions such as enhancing emotional connections through regular communication, providing parental counselling for diaspora parents, and encouraging quality visits. These findings contribute to the literature on the psychosocial effects of migration and offer policy recommendations to improve the well-being of left-behind children. The study highlights the importance of community support, educational policies, and transnational parenting strategies in fostering the holistic development of these children.